Choosing Between Lotteries: Remarkable Coordination Without Communication. (10th July 2012) - Bereby‐Meyer, Yoella; Moran, Simone; Grosskopf, Brit; Chugh, Dolly
ABSTRACT: The current research examines tacit coordination behavior in a lottery selection task . Two hundred participants in each of three experiments and 100 in a fourth choose to participate in one of two lotteries, where one lottery has a larger prize than the other. Independent of variations in the complexity of the mechanism of prize allocation, the prize amounts, and whether the lottery is the participant's first or second choice, we typically find that the percentage of participants who choose the high versus low‐prize lotteries does not significantly differ from the equilibrium predictions. This coordination is achieved without communication or experience. We additionally find that participants with an analytical thinking style and a risk‐averse tendency are more likely to choose the low‐prize lottery over the high‐prize lottery. This tendency seems to be stable across choices. The pattern of our results suggests that to achieve tacit coordination, having a subset of individuals who attend to the choices of others is sufficient. Copyright © 2012 John Wiley & Sons, Ltd.